Mutations in NPHS1 and PLCE1 (NPHS3) in two Vietnamese patients with conginetal nephrotic syndrome - Lien, Nguyen Thi Kim; Van Dem, Pham; Thu Huong, Nguyen; Minh Dien, Tran; Huy Hoang, Nguyen; Thi Quynh Huong, Nguyen (Vietnam Journal of Biotechnology, 2020)
Congenital nephrotic syndrome (CNS), a genetic disease caused by the mutations in genes on autosomes, is usually occurs in the first three months after birth. The mutations in genes that encode for the structural and functional proteins of podocytes lead to loss of the function of glomerular filtration. So far, a number of genes related to the disease have been identified such as: NPHS1, NPHS2, PLCE1 (NPHS3), ACTN4, CD2AP, INF2 and WT1. In this article, we amplified all of exons in NPHS1 and PLCE1 genes of two Vietnamese patients with CNS and members of patients’ family. PCR products were purified and sequenced directly on automatic sequencer ABI 3500 Bio System (USA). The sequencing results were compared with the sequences of NPHS1 and PLCE1 genes published in the Ensembl database (ENSG00000161270 and ENSG00000138193, respectively) by using BioEdit software to detect mutations. We identified two mutations: c.2398C>T (p.Arg800Cys, exon 18), c.3315A>G (p.Ser1105Ser, exon 26) in NPHS1 gene and two mutations: c.5330 C>T (p.Thr1777Ile, exon 23), c.5780A>G (p.His1927Arg, exon 25) in PLCE1 gene in study patients. These two patients carried simultaneously the mutations in the NPHS1 and PLCE1 genes with serious phenotype. The results of our study might be evidences for the role of mutations in NPHS1 and PLCE1 genes in the development of disease in patients. These are useful information in identifying the cause of disease and provide the genetic counseling to the patients’ family.